2022
DOI: 10.3390/jcm11030625
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electrocardiographic Signs of Right Ventricular Hypertrophy and Clot Localization in Chronic Thromboembolic Pulmonary Hypertension

Abstract: The role of electrocardiography (ECG) in chronic thromboembolic pulmonary hypertension (CTEPH) diagnosis and prognosticating has not been yet established. We aimed to assess the relationships of the recommended ECG criteria of right ventricular hypertrophy (RVH) with clot localization in CTEPH patients. ECG patterns of RVH according to the American College of Cardiology Foundation were assessed in patients with newly diagnosed CTEPH. We enrolled 58 (45.3%) patients with proximal and 70 (54.7%) with distal CTEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This observed difference in prevalence could be due to the large proportion of patients with PAH, the poorer mean haemodynamics and thus the higher cardiac workload in Waligora’s study (PVR median in the present study: 536 dyn∗sec∗cm −5 ; PVR mean in Waligora et al: 1152 dyn∗sec∗cm −5 ) [ 24 ]. However, Slawek-Szmyt et al also found an “R/S V1 > R/S in V3, V4” in 75% of their cohort, although this CTEPH cohort had demographic and haemodynamic characteristics similar to those of the present one [ 38 ]. After BPA, the frequency of the occurrence of this parameter was reduced to 10% in this present study ( p < 0.001).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This observed difference in prevalence could be due to the large proportion of patients with PAH, the poorer mean haemodynamics and thus the higher cardiac workload in Waligora’s study (PVR median in the present study: 536 dyn∗sec∗cm −5 ; PVR mean in Waligora et al: 1152 dyn∗sec∗cm −5 ) [ 24 ]. However, Slawek-Szmyt et al also found an “R/S V1 > R/S in V3, V4” in 75% of their cohort, although this CTEPH cohort had demographic and haemodynamic characteristics similar to those of the present one [ 38 ]. After BPA, the frequency of the occurrence of this parameter was reduced to 10% in this present study ( p < 0.001).…”
Section: Discussionmentioning
confidence: 80%
“…This is consistent with the results of Japanese researchers, in whose study none of the patients with CTEPH exceeded this cut-off value before or after BPA either [ 8 ]. Other studies reported a prevalence of 2–7% in PAH, CTEPH and IPAH [ 24 , 37 , 38 ]. Therefore, the assumption arises that the usefulness or the currently used cut-off value for this parameter is limited or not sensitive enough to support the diagnosis of PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed description of pulmonary angiography and CTPA procedures at our center have been previously published [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, electrocardiographic features of right ventricular hypertrophy (RVH) were analyzed in newly diagnosed CTEPH patients to differentiate between the distal and proximal clots localization. It was revealed that only 8 out of 23 ECG RVH criteria were useful for differentiating between proximal and distal CTEPH localization and RV1 and SV6 may contribute as potential discriminators [ 16 ].…”
Section: Patient Management and Selectionmentioning
confidence: 99%